Association between Lys198Asn polymorphism of endothelin‐1 gene and ischemic stroke: A meta‐analysis. Issue 10 (30th September 2019) - Nepal, Gaurav; Ojha, Rajeev; Dulal, Hari Prasad; Yadav, Binod Kumar
Abstract: Background: Endothelin (ET)‐1 is a potent vasoconstrictor peptide produced by endothelial cells and associated with vascular dysfunction and cardiovascular disease. Lys198Asn is a single‐nucleotide polymorphism (SNP) of gene encoding ET‐1 (EDN1). It is hypothesized that it might have a role in altering ET‐1 and ultimately leading to vascular dysfunction and ischemic stroke. We therefore conducted a meta‐analysis to investigate the association between Lys198Asn polymorphism of EDN1 gene and susceptibility of ischemic stroke. Methods: This meta‐analysis was conducted according to the guidance of the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement. We searched PubMed, Google Scholar, Embase, Web of Science, J‐STAGE, and China National Knowledge Infrastructure (CNKI) for relevant studies. The association between Lys198Asn polymorphism and ischemic stroke susceptibility was evaluated by calculating the pooled ORs and 95% CIs. Results: Our analysis included 1, 291 cases and 2, 513 controls. Meta‐analysis established a significant association between Lys198Asn SNP of EDN1 gene and ischemic stroke when assuming either recessive model (OR: 1.30; 95% CI: 1.02–1.65; p  = .03; I 2  = 41%) or dominant model (OR: 1.48; 95% CI: 1.24–1.76; p  < .001; I 2  = 61%). There was no evidence of publication bias in either of the recessive model (Egger test: p  = .23; Begg test: p  = .85) or dominant model (Egger test: p  = .79; Begg test: p  = .85). A subgroup analysis based on subtypes of ischemic stroke showed that Lys198Asn SNP was only associated with large vessel infarction but not with lacunar infarction caused by small vessel disease. A subgroup analysis based on ethnicity revealed that the Lys198Asn polymorphism of the EDN1 gene was associated with ischemic stroke only in Caucasians. Conclusions: The present meta‐analysis suggests that Lys198Asn polymorphism of EDN1 gene is associated with an increased risk for ischemic stroke. Abstract : Endothelin (ET)‐1 is a potent vasoconstrictor peptide produced by endothelial cells and associated with vascular dysfunction and cardiovascular disease. Lys198Asn is a single‐nucleotide polymorphism of gene encoding ET‐1 (EDN1). It is hypothesized that it might have a role in altering ET‐1 and ultimately leading to vascular dysfunction and ischemic stroke. We therefore conducted a meta‐analysis to investigate the association between Lys198Asn polymorphism of EDN1 and susceptibility of ischemic stroke. The present meta‐analysis suggests that Lys198Asn polymorphism of EDN1 gene is associated with an increased risk for ischemic stroke.